Analisis Faktor Kualitas Informasi Aplikasi SAMBARA Pajak Kendaraan Bermotor di Jawa Barat - Rizka Hayya Sabrina; Nelsi Wisna; Irman Hariman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The high level of motor vehicle tax achieved in West Java is closely linked to public awareness in paying their vehicle tax. However, tax revenues still face issues. This research investigates the impact of the Sambara application's quality on the quality of information provided. The information quality variable is crucial as it ensures users receive accurate, relevant, and timely information, affecting the overall user experience. The research aims to examine the correlation between the level of Sambara application information and the application's overall quality and measure how information quality influences the application's overall assessment. Data was acquired by administering a questionnaire using a basic random sample technique based on the motor vehicle population in West Java. The research is conducted with simple linear regression calculations to produce predictive answers and hypotheses. Results indicate a correlation of a favorable nature between the application's quality and the information quality provided. Improving the Sambara application's quality enhances the information quality received by users. The R²-Score of 0.67798 shows that approximately 67.798% of the variability in information quality assessment can be explained by the application's quality